The cranial morphology of the neotropical Microhylid (Anura) Elachistocleis Ovalis (Schneider) - Pentz, K (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1941.